Metabolic Pathways in Methanococcus jannaschii and Other Methanogenic Bacteria - Sprott, G. Dennis (1993)
Eleven strains of methanogenic bacteria were divided into two groups on the basis of the directionality (oxidative or reductive) of their citric acid pathways. These pathways were readily identified for most methanogens from the patterns of carbon atom labeling in glutamate, following growth in the presence of [2-(13)C]acetate. All used noncyclic pathways, but members of the family Methanosarcinaceae were the only methanogens found to use the oxidative direction. Methanococcus jannaschii failed to incorporate carbon from acetate despite transmembrane equilibration comparable to other weak acids. This organism was devoid of detectable activities of the acetate-incorporating enzymes acetyl coenzyme A synthetase, acetate kinase, and phosphotransacetylase. However, incorporation of [1-(13)C]-, [2-(13)C]-, or [3-(13)C]pyruvate during the growth of M. jannaschii was possible and resulted in labeling patterns indicative of a noncyclic citric acid pathway operating in the reductive direction to synthesize amino acids. Carbohydrates were labeled consistent with glucogenesis from pyruvate. Leucine, isoleucine, phenylalanine, lysine, formate, glycerol, and mevalonate were incorporated when supplied to the growth medium. Lysine was preferentially incorporated into the lipid fraction, suggesting a role as a phytanyl chain precursor.